2006
DOI: 10.4049/jimmunol.176.12.7301
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Radicals Induce Poly(ADP-Ribose) Polymerase-Dependent Cell Death in Cytotoxic Lymphocytes

Abstract: Cytotoxic T cells and NK cells will acquire features of apoptosis when exposed to oxygen radicals, but the molecular mechanisms underlying this phenomenon are incompletely understood. We have investigated the role of two enzyme systems responsible for execution of cell death, caspases and the poly(ADP-ribose) polymerase (PARP). We report that although human cytotoxic lymphocytes were only marginally protected by caspase inhibitors, PARP inhibitors completely protected lymphocytes from radical-induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…Our results are in agreement with a recent report showing involvement of AIF in death of CTL in response to reactive oxygen species [23]. Selective release of AIF during AICD of primary CTL was an unexpected finding; however, different laboratories have recently reported that different mitochondrial apoptotic proteins can be selectively released from mitochondria, without cytochrome c, in different cell death systems [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with a recent report showing involvement of AIF in death of CTL in response to reactive oxygen species [23]. Selective release of AIF during AICD of primary CTL was an unexpected finding; however, different laboratories have recently reported that different mitochondrial apoptotic proteins can be selectively released from mitochondria, without cytochrome c, in different cell death systems [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…After overnight incubation, lymphocytes were assayed for end-stage, oxidant-induced cell death by using flow cytometry based on the altered characteristics displayed by end-stage apoptotic cells, i.e., a reduced forward scatter and an increased right angle scatter (16). Apoptosis was confirmed using annexin V staining as described elsewhere (18). In some experiments, lymphocytes were exposed to MPs that were stimulated with the formylated bacterial peptide fMLF (0.1 M) or yeast cells (MP/yeast ratio of 1:4).…”
Section: Lymphocyte Cell Deathmentioning
confidence: 99%
“…After centrifugation at 380 ϫ g for 15 min, mononuclear cells were collected at the interface. The mononuclear cells were further separated into lymphocytes and MPs using a countercurrent centrifugal elutriation technique as described elsewhere (18). In brief, cells were fed into an ultracentrifuge at 2100 rpm, where the sedimentation rate of cells is balanced by a counter-directed flow through the chamber.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are antimicrobial substances that kill ingested microbes, but they may also compromise the function and viability of adjacent cells when released into the extracellular space (4,5). For example, T cells and other lymphocytes rapidly become inactivated and eventually undergo apoptosis when exposed to ROS (6)(7)(8)(9). Because effector T cells commonly exert their functions in the oxidative environment characteristic of infected or inflamed tissues (10,11), it is conceivable that T cells use strategies to escape oxygen radical-induced inactivation.…”
mentioning
confidence: 99%